European Union's Data Protection in Cyberspace for Gender Minority - Priwansyah, Rakha Hifzan; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
Data in the 21st century becomes one of the most valuable things an individual could ever possess and protect. The purpose of this study is to determine the actions taken by the European Union to secure gender minority sensitive data in cyberspace. In this research, there will be analyses of 29 European Union member states the institution responsible for collecting discrimination data towards gender minority individuals. This research uses the concept of human security, to be specific citizen personal security introduced by Costa Rican Human Development Report. Based on the using of citizen personal security concept, the results of this research show that European Union introduced data protection policy, such as General Data Protection Regulation, resulting in 8 principals which need to be satisfied in order to consider the process and use of gender minority data lawful and safe. Each of these 8 principals has passed as the form of securitibility in protecting gender minority individuals' sensitive data in cyberspace according to the citizen's personal security concept as they have reduced the probability of unlawful and misuse of sensitive data to happen.